Biocultural roles of naturalized alien plants in highland communities of Central Java, Indonesia (Asian Journal of Ethnobiology, 2025)
Abstract. Sholekha AM, Restanti AD, Rohman CM, Ainaya FA, Putri NRA, Putri A, Dewangga A, Saensouk S, Setyawan AD. 2025. Biocultural roles of naturalized alien plants in highland communities of Central Java, Indonesia. Asian J Ethnobiol 8: 26-39. Naturalized alien plant species (NAPS) are often perceived as threats to biodiversity and ecosystem stability. However, in many rural communities, these species may also serve important roles in food systems, healthcare, rituals, and livelihood strategies. This study explores the ethnobotanical utilization and cultural significance of NAPS in five highland villages in Central Java, Indonesia, based on interviews with 125 respondents and field observations. A total of 143 species were documented, with the majority being used for food (39.2%) and medicinal purposes (34.5%). The Index of Cultural Significance (ICS) revealed that certain species—such as Cosmos caudatus, Curcuma longa, and Psidium guajava—are highly valued across multiple dimensions and locations. Cross-village comparisons highlighted distinct biocultural filtering processes, shaped by local ecology, demographic structure, and cultural preferences. While some NAPS were shared across villages, many were site-specific, suggesting localized knowledge systems and adaptive use patterns. The findings underscore the need for a more nuanced, culturally grounded approach to invasive species management, one that balances ecological concerns with the needs of rural livelihoods and cultural heritage. Integrating local knowledge and community participation into plant governance frameworks is essential for achieving sustainable and socially just conservation outcomes.
Keywords: Cultural significance index, ethnobotany, invasive species management, rural livelihoods, traditional knowledge